Identification of Mutations Related to Cisplatin-Resistance and Prognosis of Patients With Lung Adenocarcinoma - Li, Rui; Liu, Junfang; Fang, Zekui; Liang, Zhenyu; Chen, Xin (Frontiers in Pharmacology, 2020)
Lung adenocarcinoma (LUAD) is the most common histologic type of nonsmall cell lung cancer (NSCLC; approximately 60%). Platinum-based chemotherapy is the cornerstone of the treatment for patients with LUAD. However, a considerable number of patients experience tumor recurrence after cisplatin (cis-diamminedichloroplatinum(II) or CDDP) resistance. Therefore, it is particularly important to screen out primary CDDP-resistant LUAD populations, which can maximize the clinical benefits of these LUAD patients. Data for 61 LUAD cell lines were downloaded from the Genomics of Drug Sensitivity in Cancer (GDSC) database to screen for mutations related to CDDP susceptibility. We conducted whole-exome sequencing (WES) of tumors from 45 LUAD patients from Zhujiang Hospital of Southern Medical University. Subsequently, the clinical prognostic value of these mutations was further verified by using The Cancer Genome Atlas (TCGA)-LUAD cohort and our cohort (n=45). Based on the drug sensitivity data for the GDSC-LUAD cell lines and survival analysis of the TCGA-LUAD and Local-LUAD cohort, we found only one gene (GREB1) with mutations related to an increased CDDP sensitivity and worse overall survival (OS) and progression-free survival (PFS) [OS: log-rank P = 0.038, hazard ratio (HR; 95% confidence interval (95% CI)): 2.19 (0.73-6.55); PFS: log-rank P = 0.001; HR: 4.65, 95%Cl: 1.18-18.37]. The GREB1-mutant (GREB1-MT) group had a higher frequency of gene mutations. Also, gene set enrichment analysis (GSEA) and single-sample GSEA (ssGSEA) suggested that the GREB1-MT group could reduce the accumulation of intracellular drugs, increase the pumping of drugs, and enhance DNA damage repair and intracellular detoxification. This study found that GREB1 mutations may mediate the primary resistance and clinical prognosis of LUAD patients undergoing treatment with CDDP. Further functional analysis shows that GREB1 mutations are related to the known mechanism of CDDP resistance. These results suggest that GREB1 mutations may be potential biomarkers for screening CDDP-resistant LUAD patients.